2017
DOI: 10.5539/elt.v10n7p104
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Competence of the Fourth Year Students: Basis for Proposed English Language Program

Abstract: This study on level of communicative competence covering linguistic/grammatical and discourse has aimed at constructing a proposed English language program for 5 key universities in Vietnam. The descriptive method utilized was scientifically employed with comparative techniques and correlational analysis. The researcher treated the surveyed data through frequency counts, means and percentage computations, and analysis of variance/t-test to compare two main area variables. The respondents was 221 students from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
3
16
2
Order By: Relevance
“…The result of the present study was strengthened by Freeman and Murcia (2010) in their Grammar Book in which research on L2 morpheme acquisition has shown that the third person singular present tense-s inflection causes persistent problems for learners even at more advanced stages of proficiency. The findings of the study corroborate also the study made by Tuan (2017) in Vietnam that the weakest point of students in grammar is the use of verbs. The weakness of the respondents relative to verb indicates that they have low knowledge, ability, and skill in determining the function of verb that is to describe an action, state, or occurrence.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The result of the present study was strengthened by Freeman and Murcia (2010) in their Grammar Book in which research on L2 morpheme acquisition has shown that the third person singular present tense-s inflection causes persistent problems for learners even at more advanced stages of proficiency. The findings of the study corroborate also the study made by Tuan (2017) in Vietnam that the weakest point of students in grammar is the use of verbs. The weakness of the respondents relative to verb indicates that they have low knowledge, ability, and skill in determining the function of verb that is to describe an action, state, or occurrence.…”
Section: Resultssupporting
confidence: 87%
“…In the study conducted by Tuan (2017) entitled 'Communicative Competence of the Fourth Year Students: Basis for Proposed English Language Program in Vietnam', he found that the strengths and weaknesses of the respondents relative to linguistic competence are along with nouns, pronouns, and preposition. On the other hand, their weaknesses are along with verb, adverb, and interjection.…”
Section: Grammarmentioning
confidence: 99%
“…The above studies concur with the findings of Singh and Shamsudin (2009); Housen et al (2012), Kuiken and Vedder (2012), Lintunen and Makila (2014), and Tuan (2017) that competence in grammar should be equally emphasised in spoken and written forms.…”
Section: Past Studiessupporting
confidence: 90%
“…In line with Halliday (2014), Tuan (2017) noted that a speaker or a writer should be good at grammar both in writing and speaking. As mentioned earlier, Radford (2009) noted that the use of a combination of sentence structures is not only used in good writing skills but it is also applied in speech to express one's thoughts.…”
Section: (Insert Table 4)mentioning
confidence: 66%
See 1 more Smart Citation